PERFORMANCE IMPROVEMENT ANALYSIS OF THE 35,000 MSME FAMILY CHIK TOSEBAR DEVELOPMENT - Muhammad Nassa Ie; Muhammad Thoriq Al-Khairiri; Isra Jannah Yanti Zai; Khairil Anwar; Saharuddin (RADJA PUBLIKA, 2022)
Statement from the Secretary of the Ministry of Cooperatives and SMEs Agus Muharam in the National Symposium on the Global Economy in an interview he said that MSMEs are the backbone and foundation of the people's economy,